Classification of intrusive thought patterns based on differences in the mechanisms of occurrence and persistence - Hinuma, Saki; Ogishima, Hiroyoshi; Shimada, Hironori; Tanaka, Yuki; Osao, Masumi; Moriishi, Chihiro; Obata, Shugo (Frontiers in Psychiatry, 2025)
IntroductionIntrusive thoughts occurring independently of intention are symptoms of obsessive-compulsive disorders (OCD). However, they also appear in various other disorders, including substance use disorders, depression, post-traumatic stress disorder, and anxiety disorders, as well as in healthy individuals. Despite this, the diversity of intrusive thoughts remains largely unexplored. In this study, we aimed to (1) classify the factors causing intrusive thoughts as identified in previous research and (2) elucidate differences in the psychological states of intrusive thoughts.MethodsWe investigated 298 participants over 20 years old using a questionnaire that includes scales such as “obsessive-compulsive belief,” “stress responses,” “thought suppression,” and “evaluation of intrusive thoughts.” To analyze data, we applied co-clustering, a machine-learning technique, to the data obtained from the investigation.ResultsWe identified three factors that affect the occurrence of intrusive thoughts: “Negative Evaluation of Intrusive Thoughts,” “Stress Responses,” and “Excessive Control of Intrusive Thoughts.” Furthermore, based on the scoring patterns of these three factors, participants were classified into five subtypes characterized by their degree of OCD tendencies. Further analysis revealed that the three factors could not be explained by OCD tendencies. Additionally, it was found that the five subtypes employed different coping strategies.DiscussionThese findings suggest that intrusive thoughts cannot be fully explained solely by the degree of OCD tendencies, which could provide valuable insights into cognitive-behavioral support targeting the various psychological states associated with intrusive thoughts.